Enhancing photocatalytic performance of covalent organic frameworks via ionic polarization - Jiahe Zhang; Xiaoning Li; Haijun Hu; Hongwei Huang; Hui Li; Xiaodong Sun; Tianyi Ma (Nature Communications)
Abstract Covalent organic frameworks have emerged as a thriving family in the realm of photocatalysis recently, yet with concerns about their high exciton dissociation energy and sluggish charge transfer. Herein, a strategy to enhance the built-in electric field of series β-keto-enamine-based covalent organic frameworks by ionic polarization method is proposed. The ionic polarization is achieved through a distinctive post-synthetic quaternization reaction which can endow the covalent organic frameworks with separated charge centers comprising cationic skeleton and iodide counter-anions. The stronger built-in electric field generated between their cationic framework and iodide anions promotes charge transfer and exciton dissociation efficiency. Moreover, the introduced iodide anions not only serve as reaction centers with lowered H* formation energy barrier, but also act as electron extractant suppressing the recombination of electron-hole pairs. Therefore, the photocatalytic performance of the covalent organic frameworks shows notable improvement, among which the CH3I-TpPa-1 can deliver an high H2 production rate up to 9.21 mmol g−1 h−1 without any co-catalysts, representing a 42-fold increase compared to TpPa-1, being comparable to or possibly exceeding the current covalent organic framework photocatalysts with the addition of Pt co-catalysts.